Modeling of the bryostatins to the phorbol ester pharmacophore on protein kinase C. - Wender, P A (Proc Natl Acad Sci U S A, 1988)
The bryostatins are macrocyclic lactones that represent an additional structural class of potent activators of protein kinase C. These marine animal biosynthetic products are of unusual interest because they induce only a subset of the biological responses induced by the phorbol esters. We have now determined the binding affinities of naturally occurring and semisynthetic bryostatins for protein kinase C by competition analysis with [26-3H]bryostatin 4 as the radioactive ligand. Esterification of the hydroxyl group at C26 caused dramatic loss of activity as did inversion of the asymmetric center at this position. In contrast, neither of the ester groups at C7 and C20 had a major influence on activity. Computer modeling of the phorbol esters, related diterpenes, and indole alkaloids suggested that the C20, C9, and C4 oxygens of phorbol represented critical elements of the phorbol ester pharmacophore. The C26 oxygen of the bryostatins, together with the C1 and C19 oxygens, gave an excellent spatial correlation with this model, with a root-mean-square deviation of 0.16 A (compared to 0.10-0.35 A among phorbol-related diterpenes). The extension of the phorbol ester pharmacophore model to the bryostatins and its agreement with the structure-activity relations for the bryostatin class of compounds provide additional support for the validity of the model.